Indirect Functional Assessment of Obsessive-Compulsive Disorder in clinical context. (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
In Behavioral Therapy, it is necessary to know the function of behavior when planning interventions, which are individualized, efficient, and produce long-term results. The aim of this study was to identify the role of obsessive-compulsive behaviors in adolescents based on strategies of indirect functional assessment, evaluating the occurrence of these behaviors in "social", "demands", "leisure" and "alone" contexts, according to the Functional Analysis model proposed by Iwata, Dorsey, Slifer, Bauman, & Richman (1994). The results indicated that, in addition to the possible negative sensorial reinforcement produced by obsessive compulsive behaviors, the liberation of social consequences and the withdrawal of demands would be important conditions in the maintenance of OCD. The results can either indicate a multiple control of the contingencies involved in the maintenance of the evaluated responses, or a fragility of the procedure in differentiating the relevant contingencies. Additional experimental tests and the evaluation of functionally oriented interventions would confirm the hypotheses raised.
Keywords: behavior analysis; obsessive-compulsive disorder; indirect functional assessment; clinical context; clinical practice.